Total degree of maximal product of two constant intuitionistic fuzzy graphs - Indumathi, P.; Kumar, S. Santhosh; Buvaneswari, R.,; Mala, S. K. (Edelweiss Applied Science and Technology, 2024)
This paper explains about the Total degree of Maximal product of Two constant IF graphs. Fuzzy graphs are derived from crisp graphs. Various properties of IF graphs are extended from Fuzzy graphs. Maximal product of Fuzzy graph structures with applications have been discussed in different papers and extended to IF graphs. Constant IF graphs are special type of IF graphs which have same degree for all its vertices. IF Graphs have many applications including the investigation of images by image segmentation, Brain mapping etc, Maximal product of fuzzy graphs is applied in various fields like effective logistic Management, Agricultural product mapping etc. Here in this paper, the Total degree of the vertices in maximal product of Constant IF graphs are studied in detail with definition and various examples and theorems.